Advancement of electric vehicle technologies, classification of charging methodologies, and optimization strategies for sustainable development - A comprehensive review - Vikram Goud Madaram; Pabitra Kumar Biswas; Chiranjit Sain; Sudhakar Babu Thanikanti; Praveen Kumar Balachandran (Heliyon)
This comprehensive review covers the latest EV technologies, charging methods, and optimization strategies. Electric and hybrid vehicles are compared, explaining their operation and effects on energy, efficiency, and the environment. The review covers new EV charging technologies. Conductive charging (CC), the most popular method due to its simplicity and cost, is tested. Wireless power transfer (WPT) systems, which charge without cables, and their integration into urban infrastructure are also examined. Battery swap stations (BSS), which quickly recharges depleted batteries, are also reviewed for their viability and adoption issues. Electric vehicle standards like charging rate and system configuration are covered in this paper. These standards simplify electric mobility across regions and manufacturers by ensuring charging infrastructure and vehicle technology compatibility. The review evaluates algorithms and mathematical models that maximize efficiency, reduce costs, and improve charging resource accessibility. Urban planners and policymakers need these optimization strategies to improve EV infrastructure. Article ends with research ideas. It identifies knowledge gaps and suggests research to improve EV technologies and charging systems. To promote electric vehicle adoption and innovation, the recommendations address technical and socioeconomic barriers. Researchers, engineers, and decision-makers use this review to develop and implement electric vehicle technologies and infrastructure.